The multidisciplinary therapy in binge eating disorder is able to influence the interdaily stability and sleep quality?. (3rd October 2019) - Galasso, Letizia; Montaruli, Angela; Mulè, Antonino; Castelli, Lucia; Bruno, Eleonora; Caumo, Andrea; Esposito, Fabio; Roveda, Eliana
ABSTRACT: We have recently shown that rest-activity circadian rhythm significantly differed in women with Binge Eating Disorder (BED) compared to the Ctrl group. In details, patients with BED exhibited significantly reduced levels of MESOR and Amplitude with respect to the Ctrl group. In addition, in this previous study, the results of the actigraphic sleep monitoring provided no evidence of differences in sleep parameters between the two groups. We expanded the original sample obtaining a total of 28 volunteered women, 14 BED women, and 14 Ctrl. We recorded in all 28 participants a 5-day actigraphic monitoring to detect the rhythmometric parameters, interdaily stability, intradaily variability, L5, M10, and sleep parameters. During the study, BED's women group kept an individual multidisciplinary therapy lasting five weekly days, from Monday to Friday, consisting in cognitive-behavioral therapy and nutritional program, administered in outpatient care from 8:00 a.m. at 5:00 p.m. The combination of both our previous and current study supports the conclusion that the sleep quality of the BED group is significantly better compared to Ctrl. The non-parametric indexes showed how interdaily stability, significantly correlated to sleep efficiency, was higher in BED group compared to the Ctrl group, indicating a better synchronization of rest-activity circadian rhythm. In conclusion, the maintenance of a regular lifestyle, such as imposed by the multidisciplinary therapy, is important to avoid alterations in the sleep-wake cycle, particularly in patients with eating disorders.